Infant Health, Women's Fertility, and Rural Electrification in the United States, 1930–1960. (3rd April 2018) - Lewis, Joshua
Abstract : From 1930 to 1960 rural communities, mainly in the U.S. South and Southwest, gained access to electricity. In addition to lights, the benefits included easier clothes washing, refrigeration, and pumped water. This article uses differences in the timing of electricity access across rural counties to study the effects on infant mortality and fertility. Rural electrification led to substantial reductions in infant mortality but had little effect on women's fertility. The increase in electricity access between 1930 and 1960 can account for 15 to 19 percent of the decline in rural infant mortality during this period.